Describing the medical malpractice and socio-demographic characteristics of physicians and patients involved in medical malpractice complaint in Tehran - Simin Kazemi (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: Medical malpractice in Iran is a common and increasing phenomenon, the characteristics of which change over time. Therefore, it is useful and necessary to describe this phenomenon and update the data about it. The purpose of this study was to describe medical malpractice complaints and socio-demographic characteristics of patients and physicians involved in medical malpractice cases in Tehran. Materials and Methods: This descriptive cross-sectional study was performed by reviewing medical malpractice cases in Tehran Medical System Dispute Resolution Council. The study was conducted by census method and 484 medical malpractice files were studied. Data were analyzed by SPSS software version 24 and using descriptive statistics including frequency, percentage, mean and standard deviation. Results: In 298 (61.5%) cases of medical malpractice cases, the patient was referred to a physician for cosmetic procedures, and in 169 (35%) cases, patients were referred to a physician for treating a medical problem. The highest number of cases resulted in medical malpractice, 139 (37.6%), were in private clinics. Public clinics, 4 (1.1%), had the lowest frequency. Most patients were aged 31-42 years, 159(43.3%), married and 219 (59.8%), with Bachelor's degree 145 (39.2%), and low socioeconomic status 137(37%). 206 (55.7%) of the complainant patients were employed, and others were unemployed or economically inactive. The mean (SD) physicians' age was 49.6 (9.6) years. 392 (81%) physicians were male, and 92 (19%) were female. 148 (30.5%) physicians had 20 years of work experience, and 291 (60.1%) were specialists. Conclusion: Most of the patients were female, married, with a Bachelor's degree and from low socioeconomic status. Most physicians were specialists, with over twenty years of work experience.